Farelo de soja oriundo de grãos de lavoura com anomalias na alimentação de frango de corte - Cruz, Genésio de Cássio Souza (2024)
With the objective of evaluating the inclusion of soybean meal from grains from crops with anomalies in the feeding of broiler chickens from 1 to 40 days of age, a literature review was carried out highlighting the current situation of soybean production. in Brazil, the importance of soybean quality and classification, process and industrialization flowchart of soybean meal production, as well as a brief characterization of the factors that affect soybean quality, addressing important aspects of normative instruction IN nº 11/2007 , such as anomalies in soybean cultivation and damage and their possible implications for animal feeding, with the aim of introducing the reader to the topic under study, providing support for a better understanding of the processes involved with the intensification of the use of damaged soybeans to replace soybeans commercial. In this context, we seek to demonstrate the effects of using damaged soybean meal in animal feed. Damaged soybeans in their chemical composition have similar characteristics to undamaged soybeans. There is specific legislation established by the Ministry of Peruvian Agriculture and Supply (MAPA) for the classification of these grains based on a maximum limit of tolerated damage. However, the impact of using soybean meal from grains with abnormalities and its use in animal feed is still little studied. Thus, a field experiment was carried out with broiler chickens aged 1 to 40 days, using increasing levels (0, 25, 50, 75 and 100%) of soybean meal from soybeans with damaged grain content containing 7.1% of fermented grains, 1.5% of chopped grains, 21.7% of moldy grains, totaling 30.3% of damage in the research. It is concluded that diets containing damaged soybean meal with 30.30% of damages do not affect the performance, intestinal morphometry, carcass yield and commercial cuts of broiler chickens from 1 to 40 days of age.